# Integration help on physics problem

## Homework Statement F=ma
F/m = a

## The Attempt at a Solution

Fc = constant force
[/B]

(Fc-cv'^2)/m = a

(Fc-cv'^2)/m = dv' / dt' * using the primes to differentiate between v and v' during integration

dt '(Fc-cv'^2) dv'*(m)

dt' = (m/ (Fc-cv'^2)) dv'

dt' = m / [ c ((Fc/c) - v'^2) ] dv'

∫c dt' = ∫ m / ((Fc/c) - v'^2) dv'

I need a method to integrate the right hand side that will allow me to get v by itself.
*u-substitution won't work
*I can't integrate it straight through
* I can use ln
* I can't use partial fractions
* I don't think I can use any trig identities here either
*I'm not sure where to take this.

right hand side
(m*c)/Fc = ∫1/ (1- ((c*v^2)/Fc)) dv'

so I found that

∫ 1/ (A^2 - x^2) dx = 1/ (2A) * ln | (x+A)/(x-a)| + C

I can rewrite my right hand side as the below to fit the equation but what do I do with the constant (c/Fc)? Once I figure that out I can use e to get rid of ln and solve for v

∫1/ (1^2- (c/Fc)*(v^2) dv'

#### Attachments

Last edited:

kuruman
Homework Helper
Gold Member
* I can't use partial fractions
Yes you can. For problems like this, I find it useful to express the differential equation in terms of the constant terminal velocity vT and eliminate the force. Do that and see what you get.

Hint on edit: What is dv/dt when terminal velocity is reached?

haruspex
Homework Helper
Gold Member
2020 Award
using the primes to differentiate between v and v' during integration
Then you should be using v' throughout the differential equation. v only comes into play after integration.

So this is my initial equation
(Fc-cv^2) = am

the terminal speed is reach when Fc=cv^2

vter= sqrt( Fc/c)

solve for c= Fc/ (vter)^2

m* dv'/dt' = Fc- (Fc/ (vter)^2)* v^2)

m dv'/dt' = Fc(1-V^2/(vter)^2)

∫ (1-V^2/(vter)^2) dv' =∫(Fc/mc)* dt' t = t0 to t v= v0 to v

t= ((vter * Fc)/ m)* tanh^-1 (v/ vter)

v= vter*tanh( (m/Fc)/vter)

* what can I do to get rid of tanh so that the integration will be easier?

Last edited:
kuruman
Homework Helper
Gold Member
Eliminate ##F_c~##; you can always put it back in later. Then the integrand becomes$$\frac{1}{c} \left( \frac{1}{v_T^2-{v'}^2} \right).$$ You can easily write this as the sum of two fractions. Also, when you integrate remember to use limits of integration. When t' = 0, v' = 0; when t' = t, v' = v.

Last edited:
• kuruman
Homework Helper
Gold Member
I thought we eliminated the c when we plugged in the value for c so we only have Fc=Force constant
In post #2, I suggested eliminating the constant force ##F_c## not the constant ##c## in ##cv^2.## Sorry if I was not clear. There are too many letters ##c## that cause confusion. Perhaps you should call the constant driving force just ##F##. The problem doesn't call it ##F_c.##

Changed the equation to use only F
(F-cv^2) = am

the terminal speed is reach when F=cv^2

vter= sqrt( F/c)

solve for c= F/ (vter)^2

m* dv'/dt' = F- (F/ (vter)^2)* v^2)

m dv'/dt' = F(1-V^2/(vter)^2)

∫ 1/ [(1-(V/vter)^2)] dv' =(F/m)∫ dt'

kuruman
Homework Helper
Gold Member
Changed the equation to use only F
"Eliminate ##F_c##" is another way of saying "Get rid of ##F_c##". This means "Replace all occurrences of ##F_c## with ##cv_T^2.##" Then you will get the integrand in post #5 which you can split into fractions. Please read this and my previous posts carefully.

Homework Helper
Gold Member
2020 Award
"Eliminate ##F_c##" is another way of saying "Get rid of ##F_c##". This means "Replace all occurrences of ##F_c## with ##cv_T^2.##" Then you will get the integrand in post #5 which you can split into fractions. Please read this and my previous posts carefully.
If I can make a comment: I think this one can be solved by partial fractions as @kuruman has suggested in post 5, (where you ultimately get two terms that both integrate as natural logs), but inverse hyperbolic tangent also works. The OP's algebra was very sloppy in post 4, and the OP even dropped the ## t ## in their expression, or the approach they were taking should have worked.

• kuruman
kuruman
Homework Helper
Gold Member
If I can make a comment: I think this one can be solved by partial fractions as @kuruman has suggested in post 5, (where you ultimately get two terms that both integrate as natural logs), but inverse hyperbolic tangent also works. The OP's algebra was very sloppy in post 4, and the OP even dropped the ## t ## in their expression, or the approach they were taking should have worked.
I agree. However in post #4 OP is asking in the end
what can I do to get rid of tanh so that the integration will be easier?
Well, the answer can be cast as a hyperbolic tangent, at which point no further integration is needed. I assumed OP was asking for a way to do the integral bypassing hyperbolic tangents and that's why I pushed for partial fractions which is a mehtod that OP eliminated in post #1.

Changed the equation to use only F
(F-cv^2) = am

the terminal speed is reach when F=cv^2

vter= sqrt( F/c)

solve for F= c* (vter)^2

m* dv'/dt' = c* (vter)^2- cv^2)

m*dv'/dt'= c (vter)^2- v^2)

(m/c)* ∫1/ (vter^2 -v^2) dv' = ∫ dt

working with the integral only
∫1/ (vter^2 -v^2) dv' = A/ (vter -v) + B/ (vter+v)

= [A /(vter+v) +B /(vter-v)] / [ (vter+v) (vter-v)]

v=vter A = 1/(2*vter)
v=-vter B= 1/(2*vter)

[1/(2*vter) [- ∫1/(v'-vter) dv' + ∫(vter+v') dv' ]]

applying the limits of integration v0= 0 v=v
first integral

-ln(v-vter)+ln(0-vter)= ln(v-vter)+ln(vter) = ln(v-vter * vter) = ln(v*vter -vter^2)
Second integral
ln (vter+v) +ln(vter+0)= ln (vter+v) +ln(vter) = ln((vter+v)*(vter))= ln(vter^2+ vter*v)

first integral + second integral
ln(v*vter -vter^2)+ ln(vter^2+ vter*v)

now adding in the t part

t=(m/c) *1/(2*vter)*ln(vter^2 - v^2)

(2*vter*c*t/m)=ln(vter^2 - v^2)

e^((2*vter*c*t/m) )= vter^2 - v^2

v^2= vter^2 - e^((2*vter*c*t/m) )

v=sqrt( vter^2 - e^((2*vter*c*t/m) ) )

Last edited:
kuruman
Homework Helper
Gold Member
(m/c)[1/(2*vter)[ln ((vter-v)) + ln((vter+v))]
This is incorrect. You did not use the limits of integration as I indicated in post #5. Ignoring the constants up front, you have integrals of the form$$\int_0^v\frac{dv'}{v_T \pm v'}$$Each integral gives you two terms when you evaluate at the upper and lower limits, four terms overall.

This is incorrect. You did not use the limits of integration as I indicated in post #5. Ignoring the constants up front, you have integrals of the form$$\int_0^v\frac{dv'}{v_T \pm v'}$$Each integral gives you two terms when you evaluate at the upper and lower limits, four terms overall.
t=1/(2*vter)[ln (vter^2 -v^2)-2ln(vter)]

kuruman
Homework Helper
Gold Member
You must have messed up a minus sign in front of one of the integrals. Don't forget that ##ln[x+y]-ln[y] = ln[\frac{x+y}{y}]##. Use this when you evaluate each integral separately then combine the two results which have a relative negative sign between them.

You must have messed up a minus sign in front of one of the integrals. Don't forget that ##ln[x+y]-ln[y] = ln[\frac{x+y}{y}]##. Use this when you evaluate each integral separately then combine the two results which have a relative negative sign between them.

So I went back to my post #11 and made some changes to how I did the integration with the limits applied and got

t=(m/c) *1/(2*vter)*ln(vter^2 - v^2)

after simplifying

t=(m/(c*2*vter))*ln(vter^2 - v^2)

kuruman
Homework Helper
Gold Member
This is still incorrect. The argument of the logarithm must be a dimensionless quantity. There is a mistake somewhere and I suspect a minus sign error. Forum rules prevent me from posting my solution, but if you post yours, I might be able to find out where you went wrong.

This is still incorrect. The argument of the logarithm must be a dimensionless quantity. There is a mistake somewhere and I suspect a minus sign error. Forum rules prevent me from posting my solution, but if you post yours, I might be able to find out where you went wrong.
can you message it to me and I'll post it?

I have my steps showed in post #11

Homework Helper
Gold Member
2020 Award
applying the limits of integration v0= 0 v=v
first integral

ln(vter-v)-ln(vter-0)= ln(vter-v)-ln(vter) = ln ( (vter-v)/(vter)) = ln(1- (v/vter))
Right here (post 11) is where the minus sign is getting omitted. The denominator needs to be changed to ## v'-vter ## before integrating: ## \int \frac{1}{v'-vter} \, dv'=\ln|v'-vter| +C ##. If the sign of the denominator is reversed, you get a minus in front of ## ln ##.

Homework Helper
Gold Member
2020 Award
## \frac{1}{vter-v'}=-\frac{1}{v'-vter} ##. Here ## v'## is your ## x ##. ## \int \frac{1}{a-x} \neq ln|x-a| ## . Instead ## \int \frac{1}{a-x}=-ln|x-a| ##.

kuruman
Homework Helper
Gold Member
Right here (post 11) is where the minus sign is getting omitted. The denominator needs to be changed to ## v'-vter ## before integrating: ## \int \frac{1}{v'-vter} \, dv'=\ln|v'-vter| +C ##. If the sign of the denominator is reversed, you get a minus in front of ## ln ##.
Yes, but what is ##C##? The integral is not indefinite. $$\int_0^v\frac{dv'}{v_T - v'}=\ln \left(\frac{v_T-v}{v_T} \right)$$
BTW, the absolute values for the argument of the logarithm are superfluous. We are doing physics here and the result (if the math is done correctly) should exist. Here ##v## cannot be larger than the terminal velocity ##v_T##.

On edit: There should be a negative sign in front of the result as noted by @Charles Link in post #31.

Last edited:
Homework Helper
Gold Member
2020 Award
∫v0dv′vT−v′=ln(vT−v−VT)
The equation in post 20 needs a minus sign in front of the right side. It also needs absolute value signs: ## \\ ## ## \int\limits_{0}^{v} \frac{dv'}{v_T-v'} =-\int\limits_{0}^{v} \frac{dv'}{v'-v_T} =-[\ln|v-v_T|-\ln|0-v_T|]=-ln|\frac{v-v_T}{-v_T}| ##. ## \\ ## I believe I have this correct.

Last edited:
SammyS
Staff Emeritus
Homework Helper
Gold Member
This is incorrect. You did not use the limits of integration as I indicated in post #5. Ignoring the constants up front, you have integrals of the form$$\int_0^v\frac{dv'}{v_T \pm v'}$$Each integral gives you two terms when you evaluate at the upper and lower limits, four terms overall.

t=1/(2*vter)[ln (vter^2 -v^2)-2ln(vter)]
@Ashley1nOnly ,

What @kuruman was telling you was, (in addition to integration limits) , you need to do each of those integrations, one with a denominator of ##\ v_{T} + v' \,,\ ## the other with denominator ##\ v_{T} - v' \,.\ ##

That second one has a subtle twist.

so the integral now becomes

[1/(2*vter) [- ∫1/(v'-vter) dv' - ∫(v'+vter) dv' ]]

what's the purpose of switching them?

kuruman
Homework Helper
Gold Member
@Ashley1nOnly ,

What @kuruman was telling you was, (in addition to integration limits) , you need to do each of those integrations, one with a denominator of ##\ v_{T} + v' \,,\ ## the other with denominator ##\ v_{T} - v' \,.\ ##

That second one has a subtle twist.
Please read post#20 about absolute signs; it came up in the previous page. Yes, there is a subtle twist in the second term.

Please post#20 about absolute signs; it came up in the previous page. Yes, there is a subtle twist in the second term.

1/(2*vter) [- ∫1/(v'-vter) dv' - ∫(-v'-vter) dv' ]